DESIGN AND IMPLEMENTATION OF PASSIVE SONAR PROTOTYPE FOR SHIP DETECTION - Karostiani, Novia
Indonesia is the largest archipelagic country in the world. The geographical location of Indonesia, which consists of islands and many straits, has resulted in many smuggling and the entry of foreign ships. Increasing the security of the sea area needs to be improved, one of which is by increasing technology. Passive sonar is a technology that can detect foreign ships without being noticed by the target. The acoustic signal emitted by the ship can be used in passive sonar to detect the direction of the ship's arrival. In this research, passive sonar prototypes were developed using the Uniform Linear Array (UCA) model and using the power comparison algorithm. The TDOA cross correlation algorithm estimates the ship's arrival direction by initiating the ship emitting an acoustic signal at a frequency of 1000 Hz. Testing the ship's arrival direction estimation is carried out in the air medium as a basic study for further research in the water medium. The developed passive sonar prototype can detect acoustic signals in the water medium. The power comparison algorithm in air medium has the lowest average error at a distance of 0,6 m at an angle of 360° with a value of 0,4311 and at a distance of 1,2 m at an angle of 90° with a value of 0,2585. The TDOA cross correlation algorithm has the lowest average error at a distance of 0,6 m at an angle of 360° with a value of 0,01 and at a distance of 1,2 m at an angle of 270° with a value of 0,0556.